OLTP handbook - McClain, Gary R (McGraw-Hill systems design & implementation series, 1993)
Contains all the information needed to justify, select and implement an online transaction processing system. This reference includes information about formulating a strategy, evaluating vendor approaches, choosing the hardware platform, monitoring performance and troubleshooting.